2017
DOI: 10.21315/jps2017.28.1.6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dielectric Screening Function and Image Charges on Hydrogenic Donor Binding Energy in a Surface Quantum Well

Abstract: To cite this article: Abarna, R., Anitha, A. & Arulmozhi, M. (2017

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…They have reported that for Impurity States in a Gallium Arsenide Quantum Dot of Rectangular Cross-Section dimensions of the system in which the length is much larger than the radius we obtain two well-defined peaks, associated with acceptors either at the on-centre position or at the edge position in the low-dimensional system. More recently, Abarna et al [15] have reported the effect of dielectric screening on the binding energy of a hydrogenic donor in a Square Quantum well composed of vacuum/GaAs/GaAlAs, as a function of well width and Aluminum composition. Their results showed that decrease in the size of the well increases the binding energy, reaching a peak value at a particular well width.…”
Section: Introductionmentioning
confidence: 99%
“…They have reported that for Impurity States in a Gallium Arsenide Quantum Dot of Rectangular Cross-Section dimensions of the system in which the length is much larger than the radius we obtain two well-defined peaks, associated with acceptors either at the on-centre position or at the edge position in the low-dimensional system. More recently, Abarna et al [15] have reported the effect of dielectric screening on the binding energy of a hydrogenic donor in a Square Quantum well composed of vacuum/GaAs/GaAlAs, as a function of well width and Aluminum composition. Their results showed that decrease in the size of the well increases the binding energy, reaching a peak value at a particular well width.…”
Section: Introductionmentioning
confidence: 99%